Pengaruh Penggunaan Ternary Blend Fly Ash Dengan Volume Tinggi dan Abu Sekam Padi Terhadap Kuat Tekan Beton Mutu Tinggi - Sofa Rizki; Syamsul Bahri; Sulaiman Sulaiman; Hanif Hanif; Aiyub Aiyub; Cut Yusnar (Jurnal Teknologi, 2021)
This study aims to find the effect of ternary blended: cement, fly ash (FA), and rice husk ash (ASP) on the compressive strength of high-strength concrete.  The composition of FA and ASP used for cement replacement were 0%, 10% ASP, 30% FA, 10% ASP+30% FA, 10% ASP+40% FA, and 10% ASP+50% FA.  The water-cement factor (FAS) and binder used are 0.3 and 500 kg/m3 fresh concrete, respectively.  The specimens used for compressive strength is cubes of 100×100×100 mm with tests at the age of 1, 3, 7, 28, and 56 days.  The results showed that the use of 10% ASP increased the compressive strength of the concrete compared to the control concrete but required more superplasticizers.  The use of 30% FA as a cement substitute showed a decrease in compressive strength compared to control concrete but reduced the use of superplasticizer.  The use of a combination of FA and ASP as a substitute for cement showed a decrease in compressive strength under control concrete and concrete using 30% FA.  The decrease in the compressive strength of concrete with the combination of ASP and FA is beyond the initial expectation.  This may be due to the disproportionate use of FA compared to ASP so that the reaction that occurs is not optimal to form calcium silicate hydrate (CSH).  However, the use of ternary blended cement, FA, and ASP still has added values which is better workability than without using FA.